2019
DOI: 10.1111/mec.15293
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in the contribution of microbial density to inducible immune dynamics

Abstract: Immune responses evolve to balance the benefits of microbial killing against the costs of autoimmunity and energetic resource use. Models that explore the evolution of optimal immune responses generally include a term for constitutive immunity, or the level of immunological investment prior to microbial exposure, and for inducible immunity, or investment in immune function after microbial challenge. However, studies rarely consider the functional form of inducible immune responses with respect to microbial den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 46 publications
(85 reference statements)
0
24
0
Order By: Relevance
“…It has been suggested that the SPBL will remain at around the bacterial load at which the infection was controlled [19, 21]. Given that insects can show dose dependent inducible immune activation [34], and given that the antimicrobial peptide Drosocin has been shown to control E. cloacae infections and that a combination of Drosocin, Attacins and Diptericins control Pr. burhodogranariea infections [47], one could hypothesise that these AMPs are to some degree involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the SPBL will remain at around the bacterial load at which the infection was controlled [19, 21]. Given that insects can show dose dependent inducible immune activation [34], and given that the antimicrobial peptide Drosocin has been shown to control E. cloacae infections and that a combination of Drosocin, Attacins and Diptericins control Pr. burhodogranariea infections [47], one could hypothesise that these AMPs are to some degree involved.…”
Section: Discussionmentioning
confidence: 99%
“…The initial exposure dose will also determine the outcome of infection, partly because microbe density at the beginning of an infection can determine the strength of the immune response [34]. Not only is dose-dependent survival frequently reported in response to bacterial infections [19, 26, 35], but bacterial load later in the infection has been demonstrated to correlate with the initial injection dose [19, 21].…”
Section: Introductionmentioning
confidence: 99%
“…The initial collection of wild beetle populations and analysis of variation in immune gene expression among larvae from these populations has been described in detail in [15]. The current study compares these larval data (available from Data Dryad [16]) to data from adults processed at the same time (data available i).…”
Section: Methodsmentioning
confidence: 99%
“…All injected beetles were sacrificed at 8 hours post injection by flash freezing, and stored at -80°C. We extracted RNA, created cDNA, and quantified gene expression via RT-qPCR as previously described [15] using 96 degenerate primers capable of amplifying transcripts from both flour beetle species with equal 97 efficiency for four immune genes: attacin-1, defensin-1, pgrp-sc2, and ddc. In addition, we 98 quantified the expression of host reference gene rps18 and a fragment of the Bt 16s gene that has 99 been previously validated as a proxy for bacterial CFU [17].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation